Re-evaluating education in Japan and Korea : demystifying stereotypes - Park, Hyunjoon (London ; New York : Routledge, 2013)
"International comparisons of student achievement in mathematics, science, and reading have consistently shown that Japanese and Korean students outperform their peers in other parts of world. Understandably this has attracted many policymakers and researchers seeking to emulate this success, but it has also attracted strong criticism and a range of misconceptions of the Japanese and Korean education system. Directly challenging these misconceptions, which are prevalent in both academic and public discourses, this book seeks to provide a more nuanced view of the Japanese and Korean education systems. These include the idea that the highly standardized means of education makes outstanding students mediocre; that this emphasis on memorisation leads to a lack of creativity and independent thinking; that students' successes are a result of supplementary education; and that the Japanese and Korean education systems are homogenous to the point of being one single system. Using empirical data Hyunjoon Park re-evaluates the strengths and weaknesses of the existing education systems and reveals whether the issues detailed above are real or unfounded and misinformed. Offering a balanced view of the evolving and complex nature of academic achievement among Japanese and Korean students, this book will appeal to students and scholars of Asian, international and comparative education, as well as those interested in Asian society more broadly"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Education -- Japan; Education -- Korea; Academic achievement -- Japan; Academic achievement -- Korea; Comparative education; Electronic books